Radiotherapy in the Treatment of Low-Grade Gliomas - Dağdelen, Meltem; Demir, Ecem; Uzel, Ömer Erol (Cerrahpaşa Medical Journal, 2022)
Objective: In the current classification of brain tumors of the World Health Organization, various tumor histologies have been categorized under the main heading of glial tumors. The subgroup of low-grade gliomas comprises grade 2 diffuse astrocytic and oligodendroglial tumors. Methods: The primary treatment of low-grade gliomas is surgery. Safe maximal resection is the widest possible resection without causing additional neurological damage. It increases survival and reduces existing neurological symptoms. Maximal safe resection may not be achieved because of tumor infiltration or proximity to sensitive motor/sensory function areas. Although radio diagnostic and surgical technique advancements have improved, residual tumors are detected in the majority of patients. Results: Adjuvant treatment of residual low-grade gliomas is controversial. The European Organisation for Research and Treatment of Cancer (EORTC) study showed that early radiotherapy after surgery extended progression-free survival for 2 years without an overall survival benefit. After this study, it has been adopted in clinical practice that high-risk patients receive early radiotherapy and low-risk groups receive radiotherapy after progression. Certain risk factors have been determined from Radiation Therapy Oncology Group (RTOG) and EORTC studies. The high-risk factors are age over 40 years, partial resection, tumor size over 5 cm, not having isocitrate dehydrogenase mutation, and tumor progression or recurrence. Adjuvant radiotherapy and concurrent chemotherapy are recommended achieving improved progression-free survival and overall survival in patients with high-risk factors. In the low-risk group, radiotherapy may be delayed until progression. Conclusions: Low-grade gliomas are slow progressing tumors. To detect progression in follow-up, it is recommended to compare follow-up magnetic resonance images with the initial reference magnetic resonance images, not with the previous control. Cite this article as: Dağdelen M, Demir E, Uzel ÖE. Radiotherapy in the treatment of low-grade gliomas. Cerrahpaşa Med J. February 12, 2022. 46(1):1-5.